Two new species of Aphanogmus (Hymenoptera: Ceraphronidae) of economic importance reared from Cybocephalus nipponicus (Coleoptera: Cybocephalidae) - Evans, Gregory A.; Dessart, Paul; Glenn, Holly (Zootaxa, 2005)
Two new species, Aphanogmus albicoxalis and Aphanogmus inamicus are described and illustrated from specimens reared from Cybocephalus nipponicus, a cybocephalid beetle that feeds upon Aulacaspis yasumatsui, a newly introduced pest of cycads in Florida.